Structural analysis of HmtT and HmtN involved in the tailoring steps of himastatin biosynthesis. Issue 11 (20th April 2013) - Zhang, Huaidong; Chen, Jie; Wang, Hua; Xie, Yunchang; Ju, Jianhua; Yan, Yunjun; Zhang, Houjin
Abstract : Himastatin is a novel antibiotic featuring a bicyclohexadepsipeptide structure. On the himastatin biosynthesis pathway, three cytochrome P450s (HmtT, HmtN, HmtS) are responsible for the post‐tailoring of the cyclohexadepsipeptide backbone. Here we report the crystal structures of HmtT and HmtN. The overall structures of these two proteins are homologous to other cytochrome P450s. However, the exceptionally long F–G loop in HmtT has a highly unusual conformation and extends deep into the active site. As a result, the F/G helices of HmtT are both kinked. In contrast, the F/G helices of HmtN are straight. Also, the F/G helices in HmtT and HmtN take distinctive orientations, which may be a contributing factor for the substrate specificity of these two enzymes. Abstract : The CO‐difference spectra of HmtT and HmtN show absorbance at 450nm. Instead of lying at the entrance of the active site, the exceptionally long F–G loop of HmtT takes a highly unusual conformation and extends deep into the active site. As a result, both F and G helices of HmtT are kinked. The F/G helices adopt distinctive orientations in HmtT and HmtN, which may play a role in distinguishing subtle differences on the highly homologous substrates.